Strengthening of Inertial Dust Removal in Impingement Flow Dust Removal Array - HE Ge; HU Xianfeng; LIU Zekun; CHEN Kehong; WEI Wenyun; YU Hui (工程科学与技术)
Aerosol particles released into the atmosphere in industrial production cause significant harm to the environment and human health, and it is necessary to use a series of dust removal equipment at the source of aerosol emissions to control them effectively. The dust removal mechanism of inertial collision is one of the main mechanisms used in dust removal equipment commonly applied in modern industrial production. When the particle size distribution characteristics of aerosol particles to be removed are determined, this mechanism can be directionally strengthened by continuously increasing the gas velocity to improve the removal rate of both large and small particles. However, this approach results in considerable resistance loss (gas path pressure drop), and the higher the gas velocity, the greater the resistance loss becomes. After fully understanding the structural characteristics of the impingement flow dust collector, the research group proposes the arrangement of a multi-layer impingement flow dust collector array to balance the contradictory relationship between particle removal rate and pressure drop. The impingement flow dust removal array consists of dust removal columns, specifically composed of several dust removal columns uniformly arranged in three-dimensional space based on certain rules, with spacing between columns to allow the passage of dust-bearing gas. The computational fluid dynamics (CFD) method is utilized to simulate the particle removal process of the array to obtain a relatively better arrangement of the equidistant impingement flow dust collection array for subsequent experiments. The aim is to obtain the particle removal rate and gas path pressure drop under different arrangement spacing through simulation. The smaller the dust column spacing, the higher the particle removal rate, but the gas path pressure drop also increases. Therefore, to balance this contradiction, a more comprehensive evaluation of removal rate and gas path pressure drop under different spacing is conducted by introducing a filter quality factor (Q factor) to determine a better arrangement of the impingement flow dust collection array. After evaluating the final numerical simulation results using the Q factor, the arrangement mode with equal spacing of 6 mm is optimal under a gas velocity of 1.5 m/s, commonly used in industrial dust removal. Based on the numerical simulation results, the research group designs and produces a physical model of a 6 mm equidistant dust removal array for experiments. Based on the above steps, further dust removal experiments are conducted at Re = 2 131~2 787 to obtain the trend of unit discharge particle removal rate of the 6 mm equidistant array with the Stk number. Finally, the empirical formula between the removal rate of unit discharge particles and the Stk number in the range of Stk = 5.2×10-4~1.0 is obtained using a numerical fitting method, and the applicability of this empirical formula is preliminarily verified by another set of removal experiments under different Re values. At present, in the actual process of industrial dust removal, not only the removal rate and energy consumption of the gas path are considered, but also the space occupied by the equipment is a critical factor. Therefore, to adapt to the wide particle size range of dust-containing gas while considering removal rate, energy consumption, and occupied space, the research group further develops a dust collection array with cascaded impingement flow arrangement based on the previous simulation and experimental results. The main feature of this dust removal array is the uneven spacing between unit rows formed by the dust removal columns. Specifically, along the direction of the dust-laden airflow, the spacing between the unit rows gradually decreases, which narrows the flow channel, increases gas velocity between arrays, and strengthens the inertial collision mechanism, improving the overall removal rate of graded particle sizes. After preliminary optimization and design, the cascaded impingement flow dust collection array is tested in a dust collection experiment. Experimental results showed that, compared to the impingement flow dust collection array with equal spacing of 6 mm, the particle removal rate of the cascaded array is significantly improved. Taking 1 μm particles at a gas velocity of 1.5 m/s as an example, the removal rate of the cascaded impingement flow dust collection array with 15 unit rows increases by 126% compared to the 6 mm equispaced array with the same number of rows, and the correlation between removal rate and Stk number aligns with the predicted value of the previously mentioned empirical formula. The applicability of the empirical formula is further confirmed. Accordingly, the research group successively designs the equidistant and cascaded impingement flow dust removal arrays and derives the empirical formula of the removal rate through experiments. This work provides guidance for further development of dust removal arrays.